Perlawanan Perempuan Terhadap Dominasi Laki-laki: Analisis Pemikiran Feminis Kate Millet Terhadap Novel Lalita Karya Ayu Utami - Iswadi Bahardur (Madah: Jurnal Bahasa dan Sastra, 2022)
This study aims to analyze and describe the problem of female characters' resistance to male domination in Ayu Utami's Lalita, which has a patriarchal cultural background. The framework for assessing the problem applies qualitative methods with content analysis techniques. Based on the results of analysis and interpretation of text data in Lalita's novel, the findings of the problems of women's resistance to masculine domination as reflected in the character of Lalita include a) rejection of subordinate stereotypes; b) rejection of masculine domination of sexuality; c) rejection of subordination as a patriarchal mode of production; and d) the idea of ​​unifying masculine and feminine characters (androgyny). The results of this study have implications for the importance of scientific studies of literary works as socio-cultural documents of society that can provide support in the formulation of policies in the private and public spheres related to efforts to protect women from sexual violence and continuous subordination by men.